Finite element analysis of the damage and healing behavior of self-healing ceramic materials. (1st December 2016) - Ozaki, Shingo; Osada, Toshio; Nakao, Wataru
Abstract: Self-healing of crack-damaged brittle ceramics is a valuable phenomenon that counteracts the reliability decrease caused by undesired cracking during service. In this study, we developed a constitutive model to analyze the behavior of self-healing ceramic materials within the framework of a finite element method (FEM), which can describe not only an isotropic damage process under specific boundary conditions, but also self-healing at high temperatures and O2 partial pressures. The damage process was formulated based on the fracture mechanics, while self-healing was described using oxidation kinetics modeling of self-healing time. In addition, the proposed constitutive model was applied to a FE analysis of alumina/15 vol.% SiC nanocomposite materials.